Structure-function relationships in rat brainstem subnucleus interpolaris. X. Mechanisms underlying enlarged spared whisker projections after infraorbital nerve injury at birth - Jacquin, MF (J Neurosci, 1993)
Prior studies indicate that the central projections of noninfraorbital vibrissae occupy greater than normal transverse areas in the rat trigeminal brainstem complex after infraorbital nerve section at birth. Here, we assessed the development of this phenomenon and possible underlying mechanisms. Cytochrome oxidase patches representing spared supraorbital (SO) or posteroorbital (PO) whiskers in the trigeminal subnucleus interpolaris (SpVi) were not reliably larger than those on the control side 24 hr after the infraorbital lesion. By 72 hr, SO and PO patches were 91% and 28% larger than those on the control side. Reliable increases were also observed on postnatal day 5 (PND5), PND7, and PND10 for the SO (59%, 65%, 66%) and PO (23%, 44%, 51%) patches. To test the hypothesis that central reorganization reflects the maintenance of peripheral supernumerary axons, myelinated and unmyelinated axons in SO vibrissa follicles were counted at PND0, PND7, PND17, and PND60. A corollary hypothesis, that peripheral regeneration errors result in both SO and surviving infraorbital axons, contributing to central SO patches, was tested with retrograde double-labeling methods. Both hypotheses were rejected. Thus, enlargement of SO patches is not due to either the maintenance of an immature peripheral innervation pattern, or regeneration of infraorbital axons into SO follicles. To determine if the enlargement of SO and PO patches produced by infraorbital nerve section is due to an activity-dependent competitive disadvantage imposed upon infraorbital afferents, TTX or bupivicaine was applied to the intact infraorbital nerve over the first 5–9 postnatal days. Brainstem maps developed normally and SO and PO patch areas were unaffected. Thus, impulse activity-based mechanisms do not appear to contribute to injury-induced patch enlargement. To test the hypothesis that patch enlargement is due to central collateral reorganization, intra-axonal recording and staining methods were applied to control and spared-whisker primary afferents in adult rats. Total bouton or collateral numbers did not differ in SpVi; however, arbor areas were reliably larger in experimental (14,879 +/- 350 microns 2) versus control (5527 +/- 1811 microns 2) fibers.(ABSTRACT TRUNCATED AT 400 WORDS)